A Reservation Scheduler for Real-Time Operating Systems - Matschulat, David; Marcon, César A. M.; Hessel, Fabiano (Anais do Workshop de Sistemas Operacionais (WSO); 2007: Anais do IV Workshop de Sistemas Operacionais, 2007)
The increasing demand for embedded multimedia applications makes evident the need for end-to-end Quality of Service (QoS) provisioning. Particularly, operating systems, despite their location at end systems, switches or routers, must guarantee that resources under their control are adequately managed to fulfill the application requirements. This work proposes the implementation of QoS provisioning in real-time embedded systems scheduler. In order to achieve the end-to-end QoS, we propose the implementation of the control and management of QoS mechanisms in the operating system scheduler. The implementation of such mechanisms includes admission control and resource reservation, as well as process scheduling control and active monitoring of the delivered QoS. As a result, a new scheduling algorithm, named ER-EDF, is proposed and compared to previous scheduler solutions. This approach was validated through a set of benchmarks and we conclude that ER-EDF adds performance and simplified hard real-time support to real-time embedded applications.